Parametric reciprocal structures: workshop of design and fabrication - Figueiredo, Bruno (2018)
[Excerpt] Foreword: One of the central challenges that needs to be maintained throughout new structural and constructional design pedagogy is how to impart knowledge about structural and constructive concepts in a manner that enhances the capacity to understand and apply them in design. Promoted under the auspices of the International Conference on Structures and Architecture — ICSA2016, the workshop “Parametric Reciprocal Structure: workshop of design and fabrication” had it genesis in proposals developed by students of the course of Special Structures of the Master in Architecture of the School of Architecture of the University of Minho (EAUM). The solutions designed by the students focused on the design of a reciprocal structure to be built at the Design Institute of Guimarães (former Tanning Factory of Ramada). The reciprocal structures workshop was organized as part of the special structures course. The workshop involved students and staff to implement constructive solutions, in the manufacturing and in the assembling of the structure. The initiative aimed to explore architectural and structural design concepts, embracing the research of: methods and processes of designing thinking; simulation and processing tools; and manufacturing concepts and materials. The computational model Reciprocalizer, developed by Prof. Dario Parigi from the University of Aalborg, was used for the morphological design exploration. This model allows the generation of three-dimensional reciprocal grids, characterized by a high degree of freedom and formal experimentation. The proposed combination of creative aspects in the conception and construction of structures, advanced technologies and complex architectural and structural applications represents a valuable learning experience of collaborative work. [...]